Non-Fungible Token (NFT): Aplicações, propriedades e variações de mercado dos NFTs - PEREIRA, Marcus Hallyson Fernandes (2024)
The objective of this work is to show the reality of Non-Fungible Token (NFT) in the current market through research done in articles, monographs, specialized websites and digital platforms that dominate the theme. This research was based on current references from the years 2014 to the present year. In view of the research method presented, it is noted that the results were conniving and met the main objective of the work, one that this study shows in a very understandable way what NFTs are, their form of use, acquisition, commercialization, advantages, disadvantages. This new market model, being very new, still brings with it countless questions, few studies in the literature, and many doubts about its real consolidation as the domain of a lucrative market. Therefore, the illustration, the concordance of information and the real interest regarding the subject is of great relevance within the current concept of profitable digital market.